Raising Students’ Vocabulary Mastery Using Selected Game: Using Chalk Down, Turn-around for EYL Students - Sri Ningsih; Indra Bulan; Antonius Ali Wutun; Fitri Arniati (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
Based on the 2013 curriculum, students are expected to master common vocabulary in academic text. However, in reality, the above goal has not been achieved. It can be proven by the fact that students still have a common vocabulary and using incorrect words. During the pre-observation, students often experience learning obstacles while learning English. The purpose of this study was to determine the use of Chalk Down, Turn Around Game for improving students’ vocabulary mastery at grade VIII SMP Negeri 1 Bambang. This study used a pre-experimental method in the form of one class given a pre-test and post-test. The number of students involved 20 students and selected using the total sampling technique. The results of the data showed that the mean score on the post-test is higher than the pre-test (85> 60.25), and the t-test value is higher than the t-table score (11,049> 2,092) at the level of increase of 0.05 with degree freedom (df) 19. It means that the use of the Chalk Down, Turn Around Game can improve students' vocabulary.